Wokół koncepcji społeczeństwa alternatywnego — 30 lat Ruchu Społeczeństwa Alternatywnego - Antonów, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The Alternative Society Movement ASM was founded in 1983 in Gdańsk. 2013 marked the 30th anniversary of the founding of this informal youth organisation, whose jubilee was celebrated by a conference as well as academic and anarchist publications. The jubilee was also accompanied by a theatrical production, a concert of music bands and competition for student bands.
Keywords: anarchizm; Ruch Społeczeństwa Alternatywnego; Wolność i Pokój; system; rząd; lewica; wolność